Note to W. M. Jordan on István Bibó, Árpád Göncz and László Kardos - Héderváry, Claire de (1960)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): Claire de Héderváry Note on information received from Sándor Kiss, a former witness to the Committee, that István Bibó, Árpád Göncz and László Kardos had been transferred from Vác prison.